Clinical patterns, causes, and treatment of torus palatinus - Bukhari, Meisan Ali; Al Mutairi, Anfal Muteb; Al Awani, Fatimah Ahmed; Alsahli, Muhannad Mohammed; Tashkandi, Moayad Mansour; Telmisani, Duaa Abdulrahman; Al Asiri, Bushra Ahmad; Alkathiri, Norah Khaled; Babtain, Daniah Omar; Alkatheeri, Hanan Salem; Alghamdi, Fahad Abdulrahman (International Journal Of Community Medicine And Public Health, 2021)
There are two types of tori, including torus palatinus and torus mandibularis. Evidence shows that these lesions usually progress slowly, and a spontaneous growth stop is usually another characteristic. Affected patients are usually asymptomatic. However, symptoms might be reported in edentulous patients and cases when the lesion is huge. In the present study, we elaborated on the causes, clinical patterns, and treatment of torus palatinus. The etiology of the condition is unclear, and different theories were reported in the literature, suggesting that the etiology of these cases is usually attributed to environmental and genetic predisposition. It has been defined as a benign tumor that presents in the maxillary bone and is usually asymptomatic. Therefore, the diagnosis of the condition is usually easy. However, it is recommended to conduct a differential diagnosis with other relevant malignant lesions in this area. Surgical interventions are not usually needed as the condition is usually discovered accidentally. However, in cases of tori-related prosthetic or functional discomfort, surgery can be conducted.